Changes in phenolic compounds and their antioxidant capacities in jujube (Ziziphus jujuba Miller) during three edible maturity stages. (March 2016) - Wang, Bini; Huang, Qingyuan; Venkitasamy, Chandrasekar; Chai, Hongkang; Gao, Hui; Cheng, Ni; Cao, Wei; Lv, Xingang; Pan, Zhongli
Abstract: This study investigated the changes in total phenolic content (TPC), total flavonoid content (TFC), individual phenolic compound content, DPPH radical scavenging activity and antioxidant capacity measured by FRAP assay of four phenolic fractions (free, esterified, glycosided and insoluble-bound) from jujube during three edible maturity stages. The maturity stages of jujubes were established as white maturity (WM), half-red maturity (HM) and red maturity (RM). The free fraction in jujube at WM stage had the highest TPC, TFC, total phenolic acid contents, and antioxidant capacities. The phenolic contents and their activities greatly decreased with the increasing maturity stage. Caffeic acid was the most predominant in all detected phenolic compounds at WM stage, while rutin dominated at HM and RM stages. Even though most of phenolic compounds with antioxidant activity in jujube existed at the WM stage as the free form, the insoluble-bound fractions also contained a large number of phenolic compounds. Highlights: The phenolic composition in jujube and the antioxidant activities changed during three edible maturity stages. The phenolic contents and their activities greatly decreased with the increasing maturity stage. Hydrolyzing extracted insoluble-bound phenolics cannot be ignored.